The First Fossil Coelacanth from Thailand - Lionel Cavin; Haiyan Tong; Eric Buffetaut; Kamonlak Wongko; Varavudh Suteethorn; Uthumporn Deesri (Diversity, 2023)
Mawsoniidae is a family of coelacanths restricted to the Mesozoic. During the Cretaceous, mawsoniids were mainly represented by the Mawsonia/Axelrodichthy complex, long known to be from western Gondwana only (South America and Africa). This apparent biogeographical distribution then faded following the discovery of representatives in the Late Cretaceous of Laurasia (Europe and North America). We report here the presence, in the Lower Cretaceous site of Kham Phok, NE Thailand, of an angular bone referred to the Mawsonia/Axelrodichthys complex. A comparison with angulars referring to both genera found in various regions of the world between the Late Jurassic and the Late Cretaceous indicated that the distinctions between these genera, and even more so between their constituent species, are unclear. This discovery is further confirmation of the very slow morphological evolution within this lineage, which may explain why their evolutionary history appears to be disconnected, at least in part, from their geographical distribution over time.